Systematic Review and Meta-Analysis Confirms Significant Contribution of Surfactant Protein D in Chronic Obstructive Pulmonary Disease - Nandy, Debparna; Sharma, Nidhi; Senapati, Sabyasachi (Frontiers in Genetics, 2019)
ABSTRACT Background: Surfactant protein D (SFTPD) is a lung specific protein which performs several key regulatory processes to maintain overall lung function. Several infectious and immune mediated diseases have been shown to be associated with SFTPD. Recent findings have suggested serum concentration of SFTPD can be used as diagnostic or prognostic marker for chronic obstructive pulmonary disease (COPD) and acute exacerbation COPD (AECOPD). But this findings lack replication studies from different ethnic populations and meta-analysis, to establish SFTPD as reliable diagnostic or prognostic biomarker for COPD and associated conditions. Methods: We performed systematic literature search based on stringent inclusion and exclusion criteria to identify eligible studies to perform a meta-analysis. Our objective was to assess the predictibility of serum SFTPD concentration and SFTPD allelic conformation at rs721917 (C>T) with COPD and AECOPD outcome. These variables were compared between COPD and healthy controls, where mean difference (MD) and odds ratio (OR) were calculated to predict the overall effectsize. Review manager (RevMan-v5.3) software was used to analyse the data. Results:A total of eight published reports were included for this study. Comparative serum SFTPD concentration data were extracted from six studies and three studies were evaluated for assessment of genetic marker from SFTPD. Our study identified strong association of elevated serum SFTPD with COPD and AECOPD. Significant association of risk was also observed for ‘T’ allele or ‘TT’ genotype of rs721917 from SFTPD with COPD and AECOPD. Conclusion: Serum concentration and alleleic confirmation of SFTPD has a significantly high predictive value for COPD and AECOPD. Thus these can be tested further and could be applied as a predictive or prognostic marker.